1997
DOI: 10.1177/108835769701200206
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Initial Communication and Responsiveness of Learners with Multiple Disabilities

Abstract: The purpose of this article is to review pertinent issues addressed in the literature relating to communication of learners who have multiple disabilities, identify progress made in communication research and practice, and propose strategies for partners' interactions with individuals who do not use symbols for communication. This article is particularly directed toward learners who communicate in a preintentional or emerging intentional manner using nonsymbolic expressions. The enhancement of partner skills a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 35 publications
2
46
0
1
Order By: Relevance
“…Siegel-Causey and Bashinski (1997) have stressed that communication should be viewed as a triangular framework: the learner, the partner and the environmental context. Ware (1996) has done much to raise awareness about the importance of a responsive environment to facilitate effective communication.…”
Section: The Theoretical Context Of Interactive Pedagogymentioning
confidence: 99%
“…Siegel-Causey and Bashinski (1997) have stressed that communication should be viewed as a triangular framework: the learner, the partner and the environmental context. Ware (1996) has done much to raise awareness about the importance of a responsive environment to facilitate effective communication.…”
Section: The Theoretical Context Of Interactive Pedagogymentioning
confidence: 99%
“…Nonconventional nonsymbolic communicative signals are therefore highly context dependent, and significantly determined by the sender's behavioural and perceptual state [30]. The socially mediated pedagogical approaches are predicated upon the recognition that early interaction and learning take place in a dynamic social context.…”
Section: Nonconventional Nonsymbolic Communicationmentioning
confidence: 99%
“…Reese [12] reported the use of behaviour state assessment in an intervention involving one adult with profound intellectual disability. In contrast, quite a lot of attention has been paid to the communicative and contextual involvement of students with MSD, especially in relation to partner responsivity [13]. In one study, Arthur et al [14] demonstrated that a systematic programme of partner training in communication support improved the skills and knowledge of participants in relation to their interactions with students with MSD.…”
Section: Directions For Research and Evidence-based Practices With Anmentioning
confidence: 95%